Efficacy of Telmisartan Plus Amlodipine in Nonresponders to CCB Monotherapy - Steen Neldam; Dingliang Zhu; Helmut Schumacher (International Journal of Hypertension)
Hypertensive patients unable to reach blood pressure (BP) targets with antihypertensive monotherapy may be switched to a combination of two medications with complementary modes of action for improved treatment response. This post hoc analysis pools data from 2812 patients, 1891 of whom were not at goal (diastolic BP [DBP] <90 mm Hg) with amlodipine 5 mg (A5) monotherapy who subsequently switched to telmisartan 40 or 80 mg (T80)/A5 single-pill combination (SPC) or amlodipine 10 mg (A10) monotherapy, and considers an additional 921 patients, 616 of whom were not at goal with A10 monotherapy who switched to telmisartan/amlodipine SPC. Patients switched to telmisartan/amlodipine SPC achieved significantly greater BP reductions compared with continued monotherapy (P<0.0001) with reductions of −15.2/−10.9 mm Hg seen with T80/A5 after 8 weeks in patients switched from A5. BP goal (<140/90 mm Hg), systolic BP goal (<140 mm Hg), and DBP goal (<90 mm Hg) were reached by significantly more patients with telmisartan/amlodipine than with monotherapy (P<0.0001 for all comparisons; 56.1%, 69.7%, and 66.9%, resp., in patients who switched from A5 to T80/A5). Early use of such combination therapy should be considered to quickly reach BP targets, particularly in patients with added risk.